Boric acid (H₃BO₃) as flux agent of clay-based ceramics, B₂O₃ effect in clay thermal behavior and resultant ceramics properties - Hernández, María Florencia (2019)
Ceramic materials were satisfactorily processed through a dry scalable process from binary clay–boric acid (H₃BO₃) mixtures. Relevant thermal parameters were established by a multitechnique approach that included thermogravimetric, differential thermal analysis, dilatometric analysis and structural and microstructural characterization of fired samples. Both clay and boric acid thermal processes were described and correlated. The experimental textural properties evidenced a porosity decrease with sintering temperature and acid addition in the 1100–1300 °C range. The amount of glass was strongly increased by the boron oxide incorporation, confirming its fluxing capacity. X-ray diffraction, supplemented by Rietveld–Le Bail refinement, verified the presence and thermal evolution of crystalline and glassy phases. The observed microstructure was similar to other clay-based ceramics, with quartz, cristobalite and mullite grains imbibed in the silica-based glassy phase. The observed mullite phase was actually a boron mullite solid solution. Boric acid was confirmed as an adequate boron oxide source. The present study gives information for further clay-based materials design with boron oxide as fluxing agent. The dry route hypothesis was confirmed. Both formulation and firing programs can be optimized. High boron addition (5 mass%) is not recommended due to the observed partial rehydration.